2016
DOI: 10.3329/jbt.v10i1.26905
|View full text |Cite
|
Sign up to set email alerts
|

Customers’ Attitude towards E-commerce in Bangladesh: An Empirical Study on Some Selected B2C E-commerce Sites

Abstract: This study aims at identifying salient attributes of e-commerce sites in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Online shopping has minimized consumer decision-making efforts by offering greater preference, filtering information and comparing products (Billal et al , 2019). Online shoppers enjoy the convenience and ease of buying online that eliminates the inconvenience of sluggish traffic or weather (Ahamed et al , 2015; Assensoh-Kodua, 2019; Qureshi and Ahmad, 2020). Customers are entitled to gather information on low price commitment or price agreements offered by retailers via internet sites, enabling customers to make price comparisons through retailers and products (Iqbal et al , 2018; Hossain et al , 2018; Beliya et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Online shopping has minimized consumer decision-making efforts by offering greater preference, filtering information and comparing products (Billal et al , 2019). Online shoppers enjoy the convenience and ease of buying online that eliminates the inconvenience of sluggish traffic or weather (Ahamed et al , 2015; Assensoh-Kodua, 2019; Qureshi and Ahmad, 2020). Customers are entitled to gather information on low price commitment or price agreements offered by retailers via internet sites, enabling customers to make price comparisons through retailers and products (Iqbal et al , 2018; Hossain et al , 2018; Beliya et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Among the multi‐attribute attitude approaches, Fishbein’s attitude‐towards‐object model proved to be the most useful in this game meat study. In essence, the model maintains that consumers evaluate individual attributes of products as favourable or unfavourable (Ahamed, Islam, & Qaom, ; Mollah, Kim, & Choudhury, ; Schiffman & Wisenblit, ). Consequently, they have favourable attitudes towards products that they consider possessing sufficient positive attributes, and unfavourable attitudes towards products with insufficient positive attributes or too many negative attributes (Schiffman & Wisenblit, ).…”
Section: Introductionmentioning
confidence: 99%
“…Fishbein’s attitude‐towards‐the‐object model makes no direct attempt to measure the importance of individual attributes, but rather the evaluation ratings determine the importance of each attribute (Ahamed et al, ; Mowen & Minor, ; Solomon, ). Researchers have found that the evaluation ratings become more extreme as the importance of an attribute increases (Mowen & Minor, ; Yosini, ).…”
Section: Introductionmentioning
confidence: 99%
“…M-payment is recklessly growing payment method in Bangladesh. Within a very short time, mobile telecommunication reached the foremost service sector in this country by its growing network (Ahamed et al, 2015). Presently, five major telecommunication companies are operating businesses, holding a large number of subscribers along with price effective strategy.…”
Section: Introductionmentioning
confidence: 99%